A comparative DFT study on the mechanism of olefin epoxidation catalyzed by substituted binuclear peroxotungstates ([SeO4WO(O2)2MO(O2)2]n− (M = TiIV, VV, TaV, MoVI, WVI, TcVII, and ReVII)). Issue 7 (3rd December 2013) - Zhu, Bo; Lang, Zhong Ling; Yan, Li Kai; Janjua, Muhammad Ramzan Saeed Ashraf; Su, Zhong Min
<x xml:space="preserve">Abstract</x> The selective epoxidation of olefins catalyzed by substituted binuclear peroxotungstates ([SeO4WO(O2)2MO(O2)2]n− (M = TiIV, VV, TaV, MoVI, WVI, TcVII, and ReVII)) are investigated at the density functional theory level. The computational results reveal that the activation barrier corresponding to the oxygen transfer to the ethylene step decreases with M = V > Ti > Ta > Mo > W > Tc > Re. The Re and Tc substituted species can effectively improve the catalytic activity with lower Gibbs free energy barriers of 22.53 and 25.82 kcal/mol relative to the others under normal conditions. This suggests that Re and Tc center peroxo complexes would improve the catalytic performance. The higher activity of the substituted species is directly attributed to the lower energy of the σ*(OO) orbital. The reaction barriers in epoxidation process are rationalized by analyzing the atomic charge, the OO bond length, and the interaction between the substituted metal and the peroxo group of the precursor complexes. © 2013 Wiley Periodicals, Inc.